Dynamic relations between public external debt and economic growth in African countries: A curse or blessing? - Benjamin Ehikioya; Alex Omankhanlen; Godswill Osuma; Ofe Inua (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
This paper used the Johansen Cointegration test and system Generalised Method of Moments (sysGMM) to examine the dynamic relations between external debt and economic growth in 43 African countries over the period 2001-2018. The study used data from World Development Indicators (WDI) as published by the World Bank and the World Economic Outlook database as provided by the International Monetary Finance (IMF). The study provides an understanding of how the importance of external debt could be short-lived due to its misapplication. The result reveals evidence to support a long-run equilibrium relationship between external debt and economic growth in Africa. The result demonstrates that beyond a specific capacity, the short-run converges to equilibrium in the long-run and external debt would start to have a deteriorating impact on economic growth in Africa. The findings of this study reinforce the need for policymakers to ensure proper application of external debt on economic activities that would lead to sustained long-term economic performance. Moreover, the government and development partners must put in place a monitoring mechanism to ensure the efficient use of borrowed funds.
Keywords: E31; F33; F35; H63; 650; external debt; government investment; economic growth; policy; Africa